Infectivity of blood components from donors with occult hepatitis B infection – results from an Australian lookback programme. Issue 2 (19th September 2014) - Seed, C. R.; Maloney, R.; Kiely, P.; Bell, B.; Keller, A. J.; Pink, J.; the Blood Service Medical Services Lookback Team
<x xml:space="preserve">Abstract</x> Background and objectives Previous studies have demonstrated that transfused blood components from donors with occult hepatitis B virus infection (OBI) are potentially infectious. This study reports the results of an Australian lookback programme for the period subsequent to the commencement of individual donation HBV NAT in July 2010 and estimates the HBV transmission rate for components from two categories of donors, confirmed OBI and HBV inconclusive (anti‐HBc reactive with non‐discriminated NAT result). Materials and methods Using the results of lookback investigations, we estimated HBV transmission rates by donor category and type of component transfused based on the prevalence of antibodies to HBV core antigen (anti‐HBc) in recipients adjusted for the estimated prevalence in the general population. Results After subtracting the background anti‐HBc rate, we derived an adjusted transmission rate (all components) with lower and upper bounds as follows: 0·85% (0·00–2·35%) for OBI donors, 2·83% (1·23–4·33%) for inconclusive donors and 1·81% (0·21–3·31%) for total (OBI and inconclusive) donors. The median adjusted transmission rate for total donors was higher (but not statistically) for plasma (3·01%) than RCCs (2·86%), but there was no evidence of transmission for cryoprecipitate or platelets (0% for both components). Conclusion Our lookback study suggests a low (0·2–3·3%) but measurable rate of HBV transmission in Australia associated with donors with OBI and supports published evidence that at least some blood component types from OBI donors, including a proportion undetectable by ID‐NAT can transmit HBV by transfusion.